KEBUTUHAH WANITA SIMPANAN DI MANADO DITINJAU DARI HIRARKI KEBUTUHAN MASLOW - Syeren Christi Lanes Sangian; Berta Esti Prasetya (PSIKOLOGI KONSELING, 2020)
Needs are congenital within each individual and be structured of a hierarchy of needs. Everyone is trying to get fulfillment from every level of needs. The purpose of this study is describe how the fulfillment of a mistress based on Maslow’s hierarchy of needs including psychological needs, need for self-security, need for love and belongingness, need for self-esteem, and need for self-actualization. This research uses a case study approach on two participants who are mistresses. The results of this study is fulfillment of the needs of mistress including psychological needs and need for love and belongingness. Meanwhile, need for self-security, need for self-esteem, and need for self-actualization have different fulfillments for each participants.